The effect of mobile seamless inquiry media on conceptual mathematics learning outcomes in trigonometry - Juniantari, Made; Ulfa, Saida; Sariyasa; Suryawan, I Putu Pasek (Indonesian Journal of Educational Development (IJED), 2025)
The abstract nature of mathematics concepts and limited class time are key factors contributing to low conceptual mathematics learning outcomes. This issue is evident among eleventh-grade students at SMA Negeri 4 Singaraja, who have difficulties in learning abstract topics such as trigonometry. This study investigates the effect of implementing Mobile Seamless Inquiry Media (MoSIM), a digital learning strategy designed to support Inquiry-Based Learning (IBL) anytime and anywhere, on students’ conceptual mathematics learning outcomes. A quasi-experimental pretest-posttest non-equivalent control group design was employed, involving 185 eleventh-grade students selected from a population of 301 students at SMA Negeri 4 Singaraja using cluster random sampling. Conceptual learning outcomes were measured using a validated multiple-choice test and analysed through one-way ANCOVA. The results revealed a statistically significant difference between students taught using the MoSIM strategy and those taught using conventional strategies (F = 5.84, p = 0.01). Students who learned through MoSIM achieved higher adjusted post-test scores (M = 80.03; SE = 1.03) compared to those who learned through conventional strategies (M = 76.57; SE = 0.99). These findings recommend the integration of MoSIM into digital era learning environments to enhance students’ conceptual mathematics learning outcomes, especially in complex and abstract topics like trigonometry.